A Cultural Exploration of Balinese Woven Borders (Tenunan Pinggiran Saput Bali) - STEELYANA, Evy W; WAWORUNTU, Mariah; WAWORUNTU, Ine (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This paper explores the intricate relationship between Balinese woven borders, known as